Inhibition of Dendrobium bicaudatum Reinw. ex Lindl growth using Paclobutrazol for in vitro conservation - Ida Ayu, Ida Ayu Putri Darmawati; Fitriani, Yuyun; Wijana, Gede (Jurnal Hortikultura Indonesia, 2022)
D. bicaudatum orchid has become threatened with extinction. Environmental damage due to human activities and overcollection of orchids has triggered the extinction of orchids in their natural habitat. In situ and ex situ conservation measures need to be taken to reduce the threat of extinction for orchids. This research aims to investigate the effect of paclobutrazol (PBZ) on culture mediums as a plant growth inhibitor, one of which is in vitro conservation measures, and was conducted experimentally using a completely randomized design. The independent variables were the concentrations of PBZ of 0, 1, 3, and 5 mg L-1, respectively, which were added to the growing medium in the form of solid MS medium. The medium-term conservation of D.bicaudatum orchids with the addition of paclobutrazol exhibited a very significant result. Inhibition of vegetative growth such as the number of leaves and root length was exhibited by 1-5 mg L-1 PBZ, while the stem diameter, as one of the dependent variables, increased more in all treatment groups than in the control group. Reduced number of roots occurred in the groups of treatments of 1 mg L-1 PBZ and 3 mg L-1 PBZ.Keywords: extinction, in Vitro culture, reduction